The Sialic Acid Binding Activity of Human Parainfluenza Virus 3 and Mumps Virus Glycoproteins Enhances the Adherence of Group B Streptococci to HEp-2 Cells - Tong, Jie; Fu, Yuguang; Meng, Fandan; Krüger, Nadine; Valentin-Weigand, Peter; Herrler, Georg (Frontiers in Cellular and Infection Microbiology, 2018)
In the complex microenvironment of the human respiratory tract, different kinds of microorganisms may synergistically interact with each other resulting in viral-bacterial co-infections that are often associated with more severe diseases than the respective mono-infections. Human respiratory paramyxoviruses, for example parainfluenza virus type 3 (HPIV3), are common causes of respiratory diseases both in infants and a subset of adults. HPIV3 recognizes sialic acid (SA)-containing receptors on host cells. In contrast to human influenza viruses which have a preference for α2,6-linked sialic acid, HPIV3 preferentially recognize α2,3-linked sialic acids. Group B streptococci (GBS) are colonizers in the human respiratory tract. They contain a capsular polysaccharide with terminal sialic acid residues in an α2,3-linkage. In the present study, we report that HPIV3 can recognize the α2,3-linked sialic acids present on GBS. The interaction was evident not only by the binding of virions to GBS in a co-sedimentation assay, but also in the GBS binding to HPIV3-infected cells. While co-infection by GBS and HPIV3 had a delaying effect on the virus replication, it enhanced GBS adherence to virus-infected cells. To show that other human paramyxoviruses are also able to recognize the capsular sialic acid of GBS we demonstrate that GBS attaches in a sialic acid-dependent way to transfected BHK cells expressing the HN protein of mumps virus (MuV) on their surface. Overall, our results reveal a new type of synergism in the co-infection by respiratory pathogens, which is based on the recognition of α2,3-linked sialic acids. This interaction between human paramyxoviruses and GBS enhances the bacterial adherence to airway cells and thus may result in more severe disease.